S1‐Guidelines on UV phototherapy and photochemotherapy. (August 2016) - Herzinger, Thomas; Berneburg, Mark; Ghoreschi, Kamran; Gollnick, Harald; Hölzle, Erhard; Hönigsmann, Herbert; Lehmann, Percy; Peters, Thorsten; Röcken, Martin; Scharffetter‐Kochanek, Karin; Schwarz, Thomas; Simon, Jan; et al.
Summary: Known in part since antiquity, the salutary effects of sunlight again garnered increasing attention in the second half of the 19 th century. The development of a device for ultraviolet irradiation of cutaneous tuberculosis by Finnsen at the onset of the twentieth century truly marked the beginning of modern phototherapy. In dermatology, treatment methods almost exclusively use wavelengths below the visible light range (ultraviolet light). Since the early 1970s, increasingly powerful artificial light sources have become available for UVB and UVA therapy as well as the combination of UVA and photosensitizers (photochemotherapy). High structural and procedural quality standards are an essential prerequisite for the implementation of effective as well as safe phototherapy. The following guidelines outline the current consensus of leading experts in the field of phototherapy with respect to indications, contraindications, and side effects of various treatment options available. Particular focus is also on adequate UV doses at the beginning and over the further course of treatment as well as on management of side effects.